EM4 Addition Effect with Eisenia foetida Worms on Compost Characteristics as a Soil Improver - Ayu Nindyapuspa; Vivin Setiani; Ulvi Pri Astuti; Muhammad Abdulloh Azam (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
A lot of fish waste is produced by the community, both from the marketing sector and the fisheries sector, which is caught by fishermen. Almost 35% of the fish waste produced is in the form of heads, bones, innards and also fish remains that are not the main catch which are thrown away directly. Vermicomposting is one of method to reduce the amount of fish waste. The adding of livestock manure in vermicomposting will increase the quality of compost. The purpose of this research is to analyze the compost quality with the mixture of fish waste and livestock manure. The results showed that The compost that has the best quality based on SNI 19-7030-2004 is B2 with 45% fish waste, 20% cow dung and 35% sawdust with a dose of EM4 10 ml, which has a final temperature of 29ºC, pH 7, water content 41%, C-organic 19.83%, nitrogen 1.34%, phosphorus 0.36%, potassium 1.15%, and C/N ratio 14.85. Then, after incubating the soil improvement, it was found that the addition of compost can improve the chemical characteristics of the soil according to the dose given. This indicates that compost application can affect soil quality. Soil quality that has C-organic and nitrogen content according to BPT in 2009 is with the addition of a dose of 5.2 grams of vermicompost. The shortcomings of this study are that the phosphorus and potassium levels are too high.